1999
DOI: 10.1046/j.1525-1594.1999.06418.x
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics Analysis to Establish the Design Process of a Centrifugal Blood Pump: Second Report

Abstract: To establish an efficient design process for centrifugal blood pumps, the results of computational fluid dynamics (CFD) analysis were compared to the results of flow visualization tests and hemolysis tests, using the Nikkiso centrifugal blood pump. CFD analysis revealed that the radial gap greatly affected the shear stress in the outlet diffuser. The hemolysis study also indicated a similar tendency. To see the flow behind the impeller, we conducted a comparative study between models with and without washout h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 10 publications
0
43
0
1
Order By: Relevance
“…Most of the CFD modelling carried out in the CPB field has focused on the centrifugal pump. Miyazoe et al (1998Miyazoe et al ( , 1999, concluded that CFD could be a useful tool for developing blood pumps, but no direct comparisons between hemolysis tests and visualization tests were actually performed. Work reported by Pinotti and Rosa (1995), Nishida et al (1999) and Takiura et al (1998), focused on centrifugal pumps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the CFD modelling carried out in the CPB field has focused on the centrifugal pump. Miyazoe et al (1998Miyazoe et al ( , 1999, concluded that CFD could be a useful tool for developing blood pumps, but no direct comparisons between hemolysis tests and visualization tests were actually performed. Work reported by Pinotti and Rosa (1995), Nishida et al (1999) and Takiura et al (1998), focused on centrifugal pumps.…”
Section: Discussionmentioning
confidence: 99%
“…With recent independent research failing to show any advantage of using a centrifugal pump over a roller pump (Hansbro et al, 1999;Takahama et al, 1985) for short-term assist (less than 8 h), perfusionists continue to use roller pumps as the arterial pump as they are simple and cost effective. The initial expectations of the centrifugal pump led to a considerable amount of numerical simulation (Anderson et al, 2000;Bludszuweit, 1995a;Sukumar et al, 1996;Nakamura et al, 1999;Huang and Fabisiak, 1978;Miyazoe et al, 1998Miyazoe et al, , 1999Takiura et al, 1998) being carried out on this device. There has been little published literature investigating the roller pump during the past 20 years.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have examined the effect of shear stress and the exposure time for the hemolysis in the blood pump (Pinotti and Rosa 1995), whereas other Table 13.7 Coefficients for hemolysis and shear stress (Blackshear et al 1965;Heuser 1980;Wurzinger et al 1985;Giersiepen et al 1990;Song et al 2004 785 Range of τ and t -4 0 < τ < 700 57 < τ < 255 0.0034 < t < 0.6 0.007 < t < 0.7 studies have examined additionally the effect of the pressure (Mizuguchi et al 1995). Some earlier studies have analyzed the shear stress (Wood et al 1999), and some studies have analyzed the relationship between the experimental results and hemolysis test results (Miyazoe et al 1998). Various investigations have been conducted on hemolysis, including those on the effect of turbulence stress (Apel et al 2001b), the effect of stretch (Arora et al 2004), a method to estimate the volume integration of hemolysis (Garon and Farinas 2004), and the effect of the dissipation of the thrombocyte (Goubergrits and Affeld 2004).…”
Section: Cfd Of Hemolysismentioning
confidence: 99%
“…In particular, ventricular assists devices (VADs) have seen application of numerical techniques (Bludszuweit 1995, Miyazoe et al 1999, Anderson et al 2000, Apel et al 2001, Behr et al 2004b, leading to increased understanding of time-dependent flow fields inside the device, and enabling comparative studies between alternative virtual prototypes. We present our experience in CFD modeling of Baylor GYRO pump in Section 2.…”
Section: Introductionmentioning
confidence: 99%